“Happy Village” Concept Helping Villages to Face COVID-19 - Hewageegana NS, Rajapaksa; GND, Guruge (International Journal of Coronaviruses, 2021)
“Health Promoting Village” concept named as “Happy Villages” started in 2007 in Badulla District in Uva Province was a community mobilization process through which village communities have been empowered to look after their community health. The areas included were Early Childhood Care and Development (ECCD), Non-Communicable Diseases (NCD) prevention , Alcohol and drug abuse. Gender Based Violence. The programmed used many interactive tools as “Mood Chart” or “Happiness Calendar” which was giving a visualizing effect. Continuous assessments done from 2009 to 2013 showed that the Health promotion strategies used in the Happy Village concept in the Uva Province can effectively and efficiently be utilized for improvement of nutrition and achievement of milestones in children. From 2017 a National program is launched named “Happy Villages”. During the Covid 19 outbreak health promotion approaches were initiated to change in lay communities successfully. Villagers had actively engaged, collectively acted in responsible manner, and identified measures to prevent COVID-19 transmission in their households, neighbourhood and community. The use of village empowerment had become a fruitful source to face the Covid pandemic in Sri Lanka. Almost 300 “Happy Villages” around the country have made facing the Covid epidemic their chief task. Many innovative ideas and practices in facing Covid 19 pandemic at village level including a visualizing calendar to identify the risk behaviours of the family members as well as the Happiness calendar to identify the family stress levels are among them. Health promotion concept is getting rooted around the country with active participation of the villages with a multisectoral support. Continuous monitoring and evaluation and sharing best practices will show the world the effectiveness of Health Promotion and the ability of empowered people in facing pandemic situations
Keywords: Happy Villages; Happiness calendar Health Promotion; Covid pandemic